Simulasi System Dynamics Kualitas Tanah Terhadap Efisiensi Biaya dan Profit Usaha Tani di Desa Gunungsari - Amanda Putri, Elsa; Murnawan, Hery (SURYA TEKNIKA, 2025)
This study evaluates the effectiveness of soil pH enhancement and pesticide-use efficiency on operational costs and the profitability of a sustainable farming system in Gunungsari Village. In this area, rice and maize are cultivated alternately in the first and second planting seasons, heavily reliant on rainfall and irrigation. During the dry season, this dependency shifts to chemical fertilizers and water pumps, leading to a surge in operational expenses. Employing a triple bottom line approach (people, planet, profit), the methodology combines quantitative analysis via SmartPLS to identify dominant sustainability factors with system dynamics simulations in STELLA to test various policy scenarios. SmartPLS results identify soil pH as the most influential factor (44% contribution). Raising soil pH from 5.97 to 6.80 through liming and organic amendments significantly reduces reliance on urea fertilizer, lowering operational costs by 5.36–7.04% and boosting profits by 12.91% (Rice Season 1), 10.27% (Rice Season 2), 14.65% (Maize Season 1), and 13.83% (Maize Season 2). Moreover, a 20–80% increase in pesticide-use efficiency curtails production costs without sacrificing yield, supporting eco-friendly agriculture. This model provides a systemic overview of social, environmental, and economic interactions and informs data-driven policy recommendations for more efficient, adaptive, and sustainable farming.